Performance Enhancement, Training and Development In Banking Sector: A Review Paper - Dikshit, Ashish; Kumar Jain, Trilok (Journal of Advanced Research in Accounting and Finance Management, 2023)
In the present scenario of economic reforms and emerging challenges the banking industry cannot rule out the importance of training programs. It is through training and skill development that the banks meet out their profitability and productivity. Training has to be initiated as training needs assessment which forms the basis for designing, budgeting and implementing the training program. Refresher training for updating with the latest knowhow is essential even if the targeted employees are the best. The primary goal of the banks for conducting training is to equip the employees to bring about customer satisfaction by addressing the customer needs.